2007
DOI: 10.1038/ja.2007.19
|View full text |Cite
|
Sign up to set email alerts
|

Two New Antifungal Alkaloids Produced by Streptoverticillium morookaense

Abstract: A new carbazole alkaloid, streptoverticillin, and a new 2-azetidinone, streptoverticillinone, along with three known cyclodipeptides were isolated from the mycelial solid culture of Streptoverticillium morookaense. Their structures were elucidated by analysis of 1D and 2D NMR, mass spectra and optical rotation data. Two new compounds exhibited antifungal activity against Peronophythora litchii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…The antibacterial activities of the EtOH extract, as well as the PE, CHCl 3 , B, C fractions against Escherichia coli , Bacillus subtilis , Micrococcus tetragenus , and Pseudomonas fluorescens were evaluated by the hole plate diffusion method (see Experimental section 3.10 for more details) [ 6 ]. The EtOH extract and the four other fractions were individually dissolved and diluted with DMSO to obtain serial concentrations of 100, 50 and 25 mg·mL -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activities of the EtOH extract, as well as the PE, CHCl 3 , B, C fractions against Escherichia coli , Bacillus subtilis , Micrococcus tetragenus , and Pseudomonas fluorescens were evaluated by the hole plate diffusion method (see Experimental section 3.10 for more details) [ 6 ]. The EtOH extract and the four other fractions were individually dissolved and diluted with DMSO to obtain serial concentrations of 100, 50 and 25 mg·mL -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the structure of 1 was established as (1b,6a,10a)-guai-4(15)-ene-6,7,10-triol. When the modified Mosher method [8] was applied to establish the absolute configuration, 1 failed to react with (aR)-or (aS)-amethoxy-a-(trifluoromethyl)benzeneacetic acid (MTPA) in the presence of 1-ethyl-3-[3-(dimethylamino)propyl]carbodiimide hydrochloride (EDC · HCl) and catalytic N,N-dimethylpyridin-4-amine (DMAP) [9], presumably due to the hindrance of the vicinal i Pr group at C(7). This was in accordance with the attributed relative configuration of 1 as shown in Fig.…”
mentioning
confidence: 99%
“…Ampelomins C-F (3)(4)(5)(6), all obtained as white powders, had the same molecular formula, C 7 H 14 O 3 , as determined from the HRESIMS and 13 C NMR data. The 1 H and 13 C NMR spectra (Tables 1 and 2) showed that they all comprised a secondary methyl group, two methylenes, and four methines, of which three were oxygenated.…”
Section: Resultsmentioning
confidence: 99%
“…3 In continuing our study, we investigated the other metabolites of this fungus. The investigation led to the discovery of seven new polyoxygenated methyl cyclohexanoids, ampelomins A-G (1)(2)(3)(4)(5)(6)(7). We herein report the isolation, structure elucidation, biological activities, and plausible biogenetic pathway of these compounds.…”
mentioning
confidence: 95%